Political corruption and democracy in contemporary Brazil - Moisés, José Álvaro (Revista Latinoamericana de Opinión Pública, 2010)
The government of Luis Inácio Lula da Silva was affected by a serious corruption scandal involving its handling of its parliamentary support, its political party and its senior ministers in 2005. Accusations were leveled by the leader of one of the main parties forming part of the governing coalition during the president’s first mandate. In spite of this, Lula was re-elected in 2006. It is clear that although it is a questiona that affects the public perception of politics, it is not an issue that mobilizes voters to hold governments responsible and answerable to society. This article contends that, whichever the cause is, it is a consequence, alongside other determinants of corruption, of Brazilian political culture; it implies that corruption affects public’s perceptions about the quality of democracy in the country. The study tests this hypothesis empirically, along with others derived from competing approaches.